Low energy X-ray grating interferometry at the Brazilian Synchrotron - Koch, F. J.; O'Dowd, F. P.; Cardoso, M. B.; Da Silva, R. R. [UNESP]; Cavicchioli, M. [UNESP]; Ribeiro, S. J.L. [UNESP]; Schröter, T. J.; Faisal, A.; Meyer, P.; Kunka, D.; Mohr, J. (Elsevier, 2017)
Grating based X-ray differential phase contrast imaging has found a large variety of applications in the last decade. Different types of samples call for different imaging energies, and efforts have been made to establish the technique all over the spectrum used for conventional X-ray imaging. Here we present a two-grating interferometer working at 8.3 keV, implemented at the bending magnet source of the IMX beamline of the Brazilian Synchrotron Light Laboratory. The low design energy is made possible by gratings fabricated on polymer substrates, and makes the interferometer mainly suited to the investigation of light and thin samples. We investigate polymer microspheres filled with Fe2O3 nanoparticles, and find that these particles give rise to a significant visibility reduction due to small angle scattering.
Keywords: Grating interferometry; Nanocrystals; Optics; X-ray